Efektivitas Pengembangan Modul Praktikum Elastisitas Berbantuan Software Tracker - Setyaningsih, Desvika Restu; Putra, Ngurah Made Dharma (UPEJ Unnes Physics Education Journal, 2021)
This research aims to develop of practicum elasticity module assisted by tracker software. This research method used the research and development and the development model used is descriptive procedural. In this research, a Likert scale was used to determine the level of feasibility and student responses to modules that have been developed. These stages consist of Initial observations product planning, product development, initial product trials, and product revisions. The results showed that the elasticity practicum module assisted by tracker software has relatively small uncertainty, namely 3.32%, and accuracy of 96.68%. The results of the module feasibility test get an average score of 85% with very feasible criteria. The details for the content feasibility component were 85%, the language eligibility component was 82%, the presentation feasibility component was 92% and the graphic eligibility component was 83%. While the score obtained from the responses of student respondents to the module is 91.25% with very good criteria